NMR-based diffusion pore imaging by double wave vector measurements - Kuder, Tristan Anselm; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2013)
One main interest of nuclear magnetic resonance (NMR) diffusion experiments is the investigation of boundaries such as cell membranes hindering the diffusion process. NMR diffusion measurements allow collecting the signal from the whole sample. This mainly eliminates the problem of vanishing signal at increasing resolution. It has been a longstanding question if, in principle, the exact shape of closed pores can be determined by NMR diffusion measurements. In this work, we present a method using short diffusion gradient pulses only, which is able to reveal the shape of arbitrary closed pores without relying on a priori knowledge. In comparison to former approaches, the method has reduced demands on relaxation times due to faster convergence to the diffusion long-time limit and allows for a more flexible NMR sequence design, because, e.g., stimulated echoes can be used. Copyright © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: diffusion; MRI; pore shape; porous media; q-space imaging; restrictions